Delivering vaccination messages via interactive channels: examining the interaction among threat, response efficacy, and interactivity in risk communication. Issue 4 (20th April 2016) - Kuang, Kai; Cho, Hyunyi
Abstract : New media-based interactive risk communication has gained increasing attention and importance. While extant research has focused on the main effects of interactivity on attitudinal and behavioral outcomes, little research has investigated how risk message content may interact with risk message modality such as interactivity in generating effects, or the psychological processes underlying it. In this study, we examined the interaction effect of interactivity, threat, and response efficacy on individuals' involvement with risk message, attitudes toward vaccination, and information seeking intention in the context of meningococcal vaccination through a 2 (interactivity: low, high) × 2 (threat: low, high) × 2 (response efficacy: low, high) experiment. Results indicated a significant three-way interaction among interactivity, threat, and response efficacy on message involvement: individuals with high-threat, high-response efficacy perceptions were more involved with the message when it was presented in a more interactive modality. With high-threat, low-response efficacy, the interactive modality of the message did not influence levels of message involvement. Furthermore, message involvement mediated the effect of the three-way interaction among threat, response efficacy, and interaction on information seeking intentions. Implications for future research and practice are discussed.